Mutual Coupling Optimization of Compact Microstrip Array Antenna - Lin Teng; Jingrui Pei; Shoulin Yin (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
In this paper, we perfect the mutual coupling of compact microstrip array antenna by designing a new defected ground structure. When the resonant frequency is 2.45GHz, array element spacing is 0.1 times of free space wavelength, we introduce new defected ground structure into antenna array. Then we use HFSS to make simulation and compare the changing of antenna's parameters before and after adding defected ground structure. The results demonstrate that the parameters representing mutual coupling in new model can reduce by 30dB, which effectively perfects the mutual coupling of compact microstrip array antenna.